Methods and Criteria for Assessing the Environmental Competence of Future Natural Science Teachers - Jurayeva Lola Ismatulloyevna (Researchparks Publishing, 2026)
This article analyzes the methods and criteria for assessing the environmental competence of future natural science teachers. The study examines the essence of environmental competence, its structural components, and its role in the process of pedagogical assessment. In addition, the main diagnostic methods used to assess environmental competence such as testing, questionnaires, observation, project-based assessment, portfolio assessment, and expert evaluation are scientifically substantiated. The research findings demonstrate that a comprehensive assessment of environmental competence contributes to identifying and developing teachers’ environmental knowledge, practical skills, and environmental culture.